2015
DOI: 10.1039/c4cc08028a
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-configured phenyl acridine thioxanthene dioxide as a host for efficient PhOLEDs

Abstract: A new high triplet organic semi-conductor based on a donor-spiro-acceptor design has been synthesised and used as a host material in high performance (EQE = 11.4%) sky blue phosphorescent organic light emitting diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 20 publications
1
44
0
1
Order By: Relevance
“…[32][33][34][35] As it is known that the increase of HOMO energy levels through the incorporation of phenylacridine, [36][37][38][39] indoloacridine, [40][41][42] quinolinophenothiazine 43 or quinolinophenoxazine 44 moieties instead of a fluorene core has remarkable consequences on the device performance we wish to report herein the first examples of 4-substituted SBF derivatives incorporating electronrich fragments, namely N-phenylcarbazole in 4-PhCz-SBF and trimethoxyphenyl in 4-Ph(OMe) 3 -SBF, Scheme 1. Through a detailed structure-properties relationship study with the corresponding building blocks, namely 4-phenyl-spirobifluorene (4-Ph-SBF), spirobifluorene (SBF), 1,2,3-trimethoxybenzene (Ph(OMe) 3 ) and N-phenyl-carbazole (N-PhCz), we highlight herein the remarkable influence of the C4-substituent on the electronic properties.…”
Section: Chartmentioning
confidence: 99%
“…[32][33][34][35] As it is known that the increase of HOMO energy levels through the incorporation of phenylacridine, [36][37][38][39] indoloacridine, [40][41][42] quinolinophenothiazine 43 or quinolinophenoxazine 44 moieties instead of a fluorene core has remarkable consequences on the device performance we wish to report herein the first examples of 4-substituted SBF derivatives incorporating electronrich fragments, namely N-phenylcarbazole in 4-PhCz-SBF and trimethoxyphenyl in 4-Ph(OMe) 3 -SBF, Scheme 1. Through a detailed structure-properties relationship study with the corresponding building blocks, namely 4-phenyl-spirobifluorene (4-Ph-SBF), spirobifluorene (SBF), 1,2,3-trimethoxybenzene (Ph(OMe) 3 ) and N-phenyl-carbazole (N-PhCz), we highlight herein the remarkable influence of the C4-substituent on the electronic properties.…”
Section: Chartmentioning
confidence: 99%
“…However, we will see that this angle can be modulated depending of the nature of the substituent borne by the fluorene (see part 5). In order to obtain high-efficiency PhOLEDs, a good charge balance is necessary in the host and many different building blocks have been used for this purpose such as indolocarbazole, 85 phenylacridine, 60,61,86 indoloacridine, 63 phosphine oxide, 40,53,56 pyridine, benzimidazole 68 among others. However, it has been shown that the C-C bond is significantly stronger than the C-S, C-P or C-N bonds.…”
Section: -Ph-sbfmentioning
confidence: 99%
“…More recently, another efficient molecular design based on a π-conjugation breaking induced by an insulating spiro bridge (Called Donor-Spiro-Acceptor design) has been also successfully introduced in literature. 46,[54][55][56][57][58][59][60][61][62][63] Finally, another approach widely developed in literature consists to introduce a steric congestion within the dye in order to hinder the planarization between two connected π-systems, which in turn breaks the π-conjugation between them. [64][65][66] This 'steric hindrance' strategy is most of the time performed through the incorporation of a sterically hindered ortho linkage 65,67,68 efficiently leading to a π-conjugation restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The exponential development of organic electronic leads to an always growing demand of new, highly efficient organic semiconductors (OSCs) adapted to their use in specific devices 1 including organic light-emitting diodes (OLED) based on fluorescent emitting materials, [2][3][4][5][6][7][8] or based on phosphorescent materials, [9][10][11][12][13][14][15][16][17][18][19] organic field-effect transistor (OFET) [20][21][22][23][24] or organic photovoltaic (OPV). 1,25 Historically, in the field of OFETs, the design of p-type materials (hole-transporting) such as pentacene, 26 oligothiophene 27 or bridged oligoarylene [28][29] 33 (see 1-4 structures in Chart 1).…”
Section: Introductionmentioning
confidence: 99%